An Expeditious Route for the Synthesis of Thiadiazolo - Pyrimidin - 2- Thiones Using Microwaves - Mishra, A. D. (Tribhuvan University Journal, 2010)
A series of 1-(1,3,4-thiadiazolo)-2-thioxo-pyrimidines 4a-g are synthesized by the condensation of monosubsituted thioureas la-g, ethyl acetoacetate 2 and arylaldehyde 3 in dry media using microwave irradiation. The reactions are completed in very short time with high yield. The use of inorganic solid supports has been proved as an alternative mean of synthetic media.